AN ANALYSIS OF THE DETERMINANTS OF FARMERS’ WELL-BEING FROM AN ISLAMIC ECONOMIC PERSPECTIVE (A CASE STUDY OF A FARMERS GROUP IN PAYA BAKUNG VILLAGE) - Rahmadini, Selfi Okta; Tambunan, Khairina; Rahma, Tri Inda Fadhila (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
Abstract This study aims to analyze the determinants of farmers’ welfare in Paya Bakung Village through an Islamic economics perspective by examining the influence of land area, education level, and farming income. This research employed a quantitative approach involving 80 respondents selected using the Slovin formula. The data were analyzed using multiple linear regression to determine both partial and simultaneous effects of the variables. The results showed that simultaneously, the four variables contributed 88.7% to the variation in farmers’ welfare, with farming income emerging as the most dominant factor. Although material aspects such as income and land area significantly influenced welfare, the Islamic economic perspective emphasizes that true welfare is not solely measured by material achievement, but also includes the dimension of falah, which encompasses blessings, psychological well-being, and distributive justice. Therefore, economic strengthening in the agricultural sector should be accompanied by resource management that aligns with sharia principles in order to create comprehensive welfare for rural communities. Keywords: Planning, Transparency, Public Welfare, Village Fund, Program Success